STRATIGRAPHIC INTERPRETATION OF THE MIDDLE MIOCENE DELTAIC SEDIMENT IN THE SANGATTA AREA, BASED ON QUANTITATIVE PALYNOLOGICAL DATA - Eko Budi Budi Lelono (Scientific Contributions Oil and Gas, 2003)
This study demonstrates the ability of palynology in helping explorationist to comprehend the stratigraphic framework of the middle Miocene formation in the Sangatta area.